1990
DOI: 10.1142/s0192415x90000162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single Moxibustion on Cutaneous Blood Vessel and Microvascular Permeability in Mice

Abstract: The effects of a single cone moxibustion on cutaneous blood vessel and microvascular permeability in ddY mice have been studied by microscopical observation and by the dye leakage technique. In our results, moxibustion induced some kind of inflammatory response such as the blood vessel reaction with leukocytes exudation and the enhancement of microvascular permeability, which is considered one of the host defense mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Some people think that this treatment is essentially a physical thermal effect [33]. Other experiments have confirmed that a single Zhuang (unit of dosage of moxibustion) of moxa cone (2 mg) moxibustion administered to the mouse abdomen can raise the temperature of the mouse's skin to 130°C and that of the area beneath the skin to 56°C [34]. Some have observed the impact of moxibustion at different distances on local skin temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Some people think that this treatment is essentially a physical thermal effect [33]. Other experiments have confirmed that a single Zhuang (unit of dosage of moxibustion) of moxa cone (2 mg) moxibustion administered to the mouse abdomen can raise the temperature of the mouse's skin to 130°C and that of the area beneath the skin to 56°C [34]. Some have observed the impact of moxibustion at different distances on local skin temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Experiment confirmed that single Zhuang (a dose unit of moxibustion) of moxa cone (2 mg) moxibustion on mice abdomen can raise the temperature to 130°C outside the skin of the point and 56°C inside the skin; the same changes of temperature were not observed in the forelimb far away from the stimulation site [8]. By using 50 mg moxa cone direct moxibustion on the skin of mice with thermocouple implanted, the temperatures of epidermal, subcutaneous, and basal layers were different; the results suggested that moxibustion thermal stimulation affects both shallow and deep tissues of the skin [9].…”
Section: Mechanism Research Of Moxibustionmentioning
confidence: 92%
“…Effects of moxibustion on the skin can appear as hottness, flushing, pain, blisters, and other skin irritations and burns phenomena. Moxibustion can lead to vasoconstriction at the burning point while vasodilatation around the point and increase peripheral arterial blood flow and microvascular permeability [8, 19]. Another thermal effect of moxibustion is to induce heat shock proteins (HSPs) in local tissues.…”
Section: Mechanism Research Of Moxibustionmentioning
confidence: 99%
“…Acupuncture stimulation, which involves thrusting or twisting needles, results in various biochemical reactions that can have effects throughout the body; moxibustion uses heat stimulation at various temperatures, from mild skin warmth to tissue damage caused by burning. This heat stimulation can yield inflammatory responses and induce vasodilation by releasing mediators such as histamine and substance P around the site of moxibustion therapy [22,23]. According to TCM, the treatment of PD in clinical practice is usually started before menstruation.…”
Section: Introductionmentioning
confidence: 99%